Pequi (Caryocar brasiliense Cambess)-Loaded Nanoemulsion, Orally Delivered, Modulates Inflammation in LPS-Induced Acute Lung Injury in Mice - Diego de Sá Coutinho; Jader Pires; Hyago Gomes; Adriana Raffin Pohlmann; Sílvia Stanisçuaski Guterres; Patrícia Machado Rodrigues e Silva; Marco Aurelio Martins; Stela Regina Ferrarini; Andressa Bernardi (MDPI AG, 2020)
Pequi is a Brazilian fruit used in folk medicine for pulmonary diseases treatment, but its oil presents bioavailability limitations. The use of nanocarriers can overcome this limitation. We developed nanoemulsions containing pequi oil (pequi-NE) and evaluated their effects in a lipopolysaccharide (LPS)-induced lung injury model. Free pequi oil or pequi-NE (20 mg/kg) was orally administered to A/J mice 16 and 4 h prior to intranasal LPS exposure, and the analyses were performed 24 h after LPS provocation. The physicochemical results revealed that pequi-NE comprised particles with mean diameter of 174-223 nm, low polydispersity index (0.11 ± 0.01), zeta potential of −7.13 ± 0.08 mV, and pH of 5.83 ± 0.12. In vivo evaluation showed that free pequi oil pretreatment reduced the influx of inflammatory cells into bronchoalveolar fluid (BALF), while pequi-NE completely abolished leukocyte accumulation. Moreover, pequi-NE, but not free pequi oil, reduced myeloperoxidase (MPO), TNF-α, IL-1β, IL-6, MCP-1, and KC levels. Similar anti-inflammatory effects were observed when LPS-exposed animals were pre-treated with the nanoemulsion containing pequi or oleic acid. These results suggest that the use of nanoemulsions as carriers enhances the anti-inflammatory properties of oleic acid-containing pequi oil. Moreover, pequi's beneficial effect is likely due its high levels of oleic acid.